Evidence for Allelopathic Activity of Mikania micrantha H.B.K. on Three Weed Species - B. S., Ismail; Mah, Lay Suat (Universiti Putra Malaysia Press, 1994)
Laboratory, greenhouse and field studies were conducted to determine the allelopathic potential of Mikania micrantha H.B.K. on the germination and growth of three weed species, A.systasia gangetica (L.) T. Anders., Chrysopogon aciculatus (Ritz.) Trin and Paspalum conjugatum Berg. Germination and fresh weight of all three weeds decreased progressively when exposed to increasing concentrations of aqueous leaf or root extract of Mikania. The phytotoxic effect of root extract on the radicle elongation of the test species was greater than that of leaf extract. The dry weight and rate of emergence of the bioassay species used were affected when Mikania debris (leaf or root) were placed on soil surfaces or incorporated into the soil. P. conjugatum emergence was strongly affected when Mikania (root orleaf) was incorporated into the soil. Soil collectedfrom the field where Mikania had been growing had no effecton the final germination of the three weed species. However, dry weights of A. gangetica and P. conjugatum were significantly reduced when grown in the Mikanilt-infested soi